2020
DOI: 10.1021/acs.jchemed.9b00820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing CeO2–NiTiO3/Attapulgite and Investigating the Conversion Rate of NOx, Sulfur Resistance, N2 Selectivity, and Stability of the Catalyst through Applied SCR by Upper-Level Undergraduate Students

Abstract: This comprehensive experiment is specially designed for the third-year and above students who are majoring in chemistry, applied chemistry, and chemical engineering. Students conduct experiments in groups, which are required to synthesize the CeO2–NiTiO3/attapulgite (ATTP) composite catalyst by the sol–gel method; the resulting catalysts are further used in the research of low-temperature selective catalytic reduction (SCR) denitration to investigate the conversion rate of NO x , sulfur resistance, N2 selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Xie et al reported a CeO 2 -NiTiO 3 /ATTP catalyst by the sol-gel method and found that its NO conversion rate decreased from 80 % to 62 % when SO 2 was fed. [14] Recently, Ma et al introduced a hollowstructured CeO 2 -TiO 2 catalyst synthesized by solvothermal method, with a NO conversion of 73 % at 300°C. However it declined sharply to 20 % in the presence of SO 2 during the 40hour stability test.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al reported a CeO 2 -NiTiO 3 /ATTP catalyst by the sol-gel method and found that its NO conversion rate decreased from 80 % to 62 % when SO 2 was fed. [14] Recently, Ma et al introduced a hollowstructured CeO 2 -TiO 2 catalyst synthesized by solvothermal method, with a NO conversion of 73 % at 300°C. However it declined sharply to 20 % in the presence of SO 2 during the 40hour stability test.…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas is a clean and high-quality energy source . Faced with economic and environmental pressures, , the demand for natural gas has gradually increased in many countries . Combining clean hydrogen with abundant CO/CO 2 by methanation (eqs –) has been intensified in the past decade as this process can relieve pressure on energy supply and is carbon neutral. …”
mentioning
confidence: 99%
“…In this journal, several papers have reported the heterogeneous catalytic process , and the catalytic reduction of NOx, bromates, and methyl oleate for undergraduate experiments. ,, Only a few CO/CO 2 conversion experiments have been presented for undergraduates despite the importance of this synthesis process in real-world applications. , Rubner et al described educational modules on the power-to-gas concept using Sabatier’s reaction (CO 2 methanation) as an example to show a path to renewable energy. This work only provides a science education curriculum for first-year undergraduate students or the general public.…”
mentioning
confidence: 99%